Effect of Consuming Salmon Products on Vitamin D Status of Young Caucasian Women in Autumn—A Randomized 8-Week Dietary VISA 2 (Vitamin D in Salmon Part 2) Intervention Study - Zofia Utri-Khodadady; Dominika Głąbska; Dominika Guzek (Nutrients, 2024)
Background/Objectives: Young women are often at risk of vitamin D deficiency, while fatty fish can provide significant amounts of it, which is especially important when no vitamin D skin synthesis is possible due to limited sunshine exposure. This study aimed to analyze the impact of increasing the intake of salmon in various forms (smoked salmon, salmon sausages) on vitamin D status of young women in autumn. Methods: The 8-week intervention involved 120 non-obese women, aged 20–25 years. Participants were randomly assigned to one of three groups: smoked salmon (25 g/day), salmon sausage (100 g/day), or a control group. Both intervention products provided approximately 5 µg of vitamin D daily. Serum concentrations of 25(OH)D as well as vitamin D intakes were assessed pre-, mid-, and post-intervention. Results: The median vitamin D intake at baseline was 2.7–3.4 µg/day and did not differ between the groups (p > 0.05), while during the intervention, it was highest in the smoked salmon group (p < 0.001) and amounted to 7.3 µg/day. While all groups experienced a decrease in 25(OH)D serum concentrations, the decrease was significantly smaller in the salmon sausage group compared to the control group (−4.3 vs. −15.0 nmol/L, p < 0.05), and no significant difference was observed between the smoked salmon and control group after 8 weeks (p > 0.05). Moreover, in the salmon sausage group, the intervention was more effective among participants with an inadequate vitamin D status at baseline (25(OH)D change after the intervention: −3.0 vs. −5.4 nmol/L, p < 0.05; inadequate vs. adequate baseline vitamin D status). Conclusions: Increasing the intake of salmon, and hence of vitamin D, was not enough to maintain the vitamin D status of young women in autumn. It seems that other, not-yet-fully-understood factors, may influence vitamin D absorption and/or metabolism, thereby affecting the outcomes of such interventions indicating that further research is needed. Nevertheless, it may be concluded that increasing ...